Influence of carboxylated and phosphonated single‐walled carbon nanotubes on the transport properties of sulfonated poly(styrene‐isobutylene‐styrene) membranes. Issue 21 (2nd October 2018) - Ruiz‐Colón, Eduardo; Pérez‐Pérez, Maritza; Suleiman, David
ABSTRACT: This study discusses the effect of carboxylated (COOH) and phosphonated (PO3 H2 ) single‐walled carbon nanotubes (SWCNTs) on the transport properties of sulfonated poly(styrene‐isobutylene‐styrene) (SO3 H SIBS) as polymer nanocomposite membranes (PNMs) for direct methanol fuel cell (DMFC) and chemical and biological protective clothing (CBPC) applications. The properties were determined as a function of sulfonation level of SIBS, SWCNTs functionalization and loading. A comprehensive materials characterization study was performed to understand the interactions between the nanofillers and the functionalized polymer matrix, and to determine the effect of their incorporation on the resulting nanostructure of the PNMs. Results indicate that the sulfonation level is the variable that dictates nanofiller dispersion, mechanical properties, water absorption capabilities, morphology, and oxidative stability of SO3 H SIBS. Meanwhile, the nanofiller loading and functionalization influenced the transport properties. The nanofillers reduced methanol permeation. PO3 H2 SWCNTs increased the proton conductivity but at a high sulfonation level (i.e., 90 mol %), the ionic interconnectivity caused a more complex morphology decreasing the transport of protons. Optimal selectivity in transport properties were found with a sulfonation level of 61 mol % and a PO3 H2 SWCNTs loading of 1.0 wt. % for DMFC and 0.5 wt. % for CBPC due to changes in morphology and the unique transport mechanism of permeants through the PNMs. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2018, 56, 2475–2495 Abstract : Polymer nanocomposite membranes were prepared for direct methanol fuel cell and chemical and biological protective clothing applications. Carboxylated and phosphonated single‐walled carbon nanotubes were incorporated into sulfonated poly(styrene‐isobutylene‐styrene) and the transport properties were studied per sulfonation level, and nanofiller loading and functionalization. A characterization study was performed to understand the interactions between the ionic groups and the resulting nanostructure. The intermediate sulfonation level and high loadings of the phosphonated nanofiller provided optimum transport properties.